Rhetorical Move Metode Riset dalam Artikel Ilmiah Berbahasa Arab: Perbandingan Penulis Arab dan Indonesia - Aulia, Novica; Syihabuddin, Syihabuddin; Supriadi, Rinaldi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to analyze the rhetorical structure of the methodology section in Arabic-language scientific articles written by native Arabic speakers and Indonesian speakers, particularly in linguistics and education. Using a qualitative approach and content analysis method, the study applies Zhang and Wannaruk’s (2016) Move and Step framework to identify rhetorical patterns and examine the use of tense and voice in the methodology section. The data were obtained from 80 journal articles—40 in education and 40 in linguistics—equally divided between Arab and Indonesian authors, selected through purposive sampling. The findings show that Move 2 (describing data collection procedures) is the most dominant (56.9%), indicating that the majority of authors place greater emphasis on technical and procedural aspects rather than research design (Move 1: 19.5%) or data analysis procedures (Move 3: 23.5%). Indonesian authors focus more on Move 2 (62.7%) than Arab authors (51.7%), while Arab authors demonstrate a more balanced structure across the three Moves. From a linguistic perspective, it was found that the use of Māḍi (past tense) is more dominant than Muḍāri’(present tense), especially in Moves 1 and 2, as these parts describe processes already carried out. Active voice is more frequently used in Moves 1 and 2, while passive voice is more dominant in Move 3 to maintain objectivity rather than emphasize the researcher’s role.